Dextran as an elicitor of phenylpropanoid and flavonoid biosynthesis in tomato fruit against gray mold infection. (1st December 2019) - Lu, Laifeng; Ji, Lifeng; Shi, Ruixi; Li, Shuhua; Zhang, Xi; Guo, Qingbin; Wang, Changlu; Qiao, Liping
Highlights: Tomato fruits perceive dextran as a pathogen-associated molecular pattern. Dextran accelerated fruit wound healing and induced systemic disease resistance. Dextran upregulated phenylpropanoid and flavonoid biosynthesis pathways in fruit. Callose deposition is involved in dextran-mediated disease resistance. Dextran increased fruit metabolites that inhibit Botrytis cinerea spore germination. Abstract: Alpha-1, 3-glucan is often synthesized on the surface of pathogenic filamentous fungi cell walls to block pathogen-associated molecular patterns (PAMPs) generation by host plant enzymes and the subsequent immune system response of the plant. Here, Botrytis cinerea susceptibility was assessed in tomato fruit to determine whether the fruit could recognize this camouflage and mount an immune response to it. The results showed that local mechanical wounds treated with dextran and laminarin, except amylopectin, could locally and then systemically activate disease resistance against B. cinerea infection in tomato fruit. Dextran treatment effectively elicited fruit callose deposition and phenylpropanoid and flavonoid biosynthesis to a greater extent than α-glucanase activity relative to the mock group surface wounds. Enzymatic hydrolysis of this polysaccharide provided some help in improving host disease resistance. Taken together, these results demonstrate that tomato fruit can perceive α-1, 3-glucan as a kind of PAMPs but have limited ability to degrade it.